Epigenetic alterations in creatine transporter deficiency: a new marker for dodecyl creatine ester therapeutic efficacy monitoring - Broca-Brisson, Léa; Disdier, Clémence; Harati, Rania; Hamoudi, Rifat; Mabondzo, Aloïse (Frontiers in Neuroscience, 2024)
Creatine transporter deficiency (CTD) is an X-linked disease caused by mutations in the Slc6a8 gene. The impaired creatine uptake in the brain leads to developmental delays with intellectual disability. We hypothesized that deficient creatine uptake in CTD cerebral cells impact methylation balance leading to alterations of genes and proteins expression by epigenetic mechanism. In this study, we determined the status of nucleic acid methylation in both Slc6a8 knockout mouse model and brain organoids derived from CTD patients’ cells. We also investigated the effect of Dodecyl Creatine Ester (DCE), a promising prodrug that increases brain creatine content in the mouse model of CTD. The level of nucleic acid methylation was significantly reduced compared to healthy controls in both in vivo and in vitro CTD models. This hypo-methylation tended to be regulated by DCE treatment in vivo. These results suggest that increased brain creatine after DCE treatment restores normal levels of DNA methylation, unveiling the potential of using DNA methylation as a marker to monitor the drug efficacy.